2014
DOI: 10.1016/j.jtcvs.2013.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Palliative pulmonary artery banding versus anatomic correction for congenitally corrected transposition of the great arteries with regressed morphologic left ventricle: Long-term results from a single center

Abstract: In patients with congenitally corrected transposition of the great arteries with deconditioned morphologic left ventricle pulmonary artery banding may be considered an ideal procedure because it allows left ventricle training while improving tricuspid regurgitation. Compared with the double-switch procedure after pulmonary artery banding, prolonged palliative pulmonary artery banding provided a lower mortality rate and indicated better cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
1
6
0
2
Order By: Relevance
“…In the current study, a notable amount (16/44, 29.5%) of deaths was directly caused by PAH crisis. The fate of the left ventricle after the DS procedure for cc-TGA remains a significant problem, especially in patients who undergo prior PAB-T [11,18], which was confirmed by our results that cardiac dysfunction was responsible for most overall deaths in the cc-TGA group.…”
Section: Concomitant Nsjr Favoring Neoaortic Valve Competencesupporting
confidence: 85%
See 1 more Smart Citation
“…In the current study, a notable amount (16/44, 29.5%) of deaths was directly caused by PAH crisis. The fate of the left ventricle after the DS procedure for cc-TGA remains a significant problem, especially in patients who undergo prior PAB-T [11,18], which was confirmed by our results that cardiac dysfunction was responsible for most overall deaths in the cc-TGA group.…”
Section: Concomitant Nsjr Favoring Neoaortic Valve Competencesupporting
confidence: 85%
“…The timing and indication of surgical intervention for patients diagnosed with cc-TGA varied according to morphologic right ventricular failure, tricuspid regurgitation, and pulmonary vascular changes. Our surgical technique, including left ventricular retraining and DS (atrial and arterial switch) operation has been previously described [11].…”
Section: Surgical Strategy and Techniquesmentioning
confidence: 99%
“…In patients with corrected transposition of the great arteries who have a systemic right ventricle, the position of the ventricular septum affects tricuspid valve competence. 17,18 The single–right ventricle anomaly population may have other variables affecting tricuspid valve function, such as leaflet or subapparatus abnormalities, 19 and the short-term nature of this study has not demonstrated the chronic effects of the left ventricle on tricuspid valve function.…”
Section: Discussionmentioning
confidence: 78%
“…Even after anatomic correction, some patients will develop subsequent systemic (left) ventricular dysfunction. 17,18,[24][25][26][27][28][29]…”
Section: Outlook For the Patient With No Or Minor Associated Lesionsmentioning
confidence: 99%